KERAGAMAN MAKROFAUNA TANAH DALAM PERTANAMAN PALAWIJA DI LAHAN KERING PADA SAAT MUSIM PENGHUJAN - Sumani Sumani; Zaidatun Nusroh; Supriyadi Supriyadi (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
The Variability of Soil Macrofauna on Palawija Cropping of Dry Land in The Rainfall Season. The variability of Soil macrofauna is the one of biological natural resources that very useful for the environment. Their existence affected by biotic and abiotic factors around them. Soil macrofauna variability that exists on the dry land in palawija cropping will be different from the vegetation of forest. The aim of this research is to know the effect of the palawija cropping to soil macrofauna variability on the dry land in the rainfall season. The research was conducted on November 2006‐April 2007. This research is descriptive explorative that has quantitative and qualitative ones with the field survey and laboratory analysis approach. The technique of determination sampling location based on purposive sampling system. The taking of sample has been done in 3 locations under 3 palawija cropping (maize, peanut, and soybean) as much 3 times replication in the rainfall times (December 2006‐Februari 2007). The result shows that palawija cropping influences non significantly to the macrofauna variability on the soil surface, soil macrofauna variability under soil surface and environment variables that have been observed unless to bulk density (influences significantly). The highest macrofauna variability on the soil surface occurs in maize cropping. Whether under soil surface macrofauna variability occurs in peanut cropping. There were five Ordos of macrofauna on the soil surface that found in maize cropping, Hymenoptera, Araneida, Orthoptera, Diplura, and Collembola (mesofauna). Ten Ordos of macrofauna under soil surface that found under peanut cropping were Hymenoptera, Isoptera, Oligochaeta, Diptera, Homoptera, Hemiptera, Orthoptera, Araneida, Lepidoptera and Collembola (mesofauna). It was found that dominancy of the ordo of macrofauna on the soil surface from ordo Hymenoptera in maize cropping and ordo Orthoptera in peanut and soybean cropping. The dominancy of soil macrofauna under soil surface was from ordo Hymenoptera and was found under maize and peanut cropping and Oligochaeta in soybean cropping. There were positive and negative functions of soil macrofauna. The positive ones are as a predator and decomposer of organic material. Whether the negative are as virus vector and plant disease. Key word: macrofauna variability, palawija cropping, and ordo of macrofauna